(untitled) (Journal of the Bangladesh Agricultural University, 2019)
Eggplant is a familiar and admired vegetable in Bangladesh. It is a highly perishable vegetable and cannot be preserved long. Drying is an ancient preservation method used to extend shelf-life of fruits and vegetables. Different Pretreatments may affect the drying kinetics of foods. A study was conducted to evaluate how pretreatments affect the drying behavior of eggplant. Proximate composition of fresh eggplant was analyzed. The samples of constant thickness (8 mm) were dried at 50°C, 55°C and 60°C to determine the effect of temperature on drying rate constant, while for determining the effect of thickness on rate constant, eggplant slices of 4, 6 and 8 mm thicknesses were dried at a constant temperature of 55°C. It was observed that, drying rate decreased with the increase in thickness and the index ‘n’ was found to be 0.89 at 55°C. Under similar drying condition at constant thickness (8 mm), drying time showed an inverse relationship with temperature. The activation energy (Ea) was calculated as 3.242 Kcal/g-mole. Eggplant slices having the highest thickness (8 mm) were blanched at 70°C, 75°C and 80°C for 1, 2 and 2.5 minutes, respectively using hot water bath to determine the effective blanching time and temperature. It was observed that the samples blanched at 75°C and 80°C for 2 minute were enough to inactivate the enzymes. Pretreated (blanched, sulphited and blanched plus sulphited) eggplant slices having constant thickness (8 mm) were dried at constant temperature of 55°C. The drying time was influenced by pretreatments. The highest drying rate was observed for eggplant slices with blanched plus sulphited (5% KMS solution) samples while eggplant slices with 5%KMS solution dipped for 10 minutes showed the lowest drying rate. In case of fresh slices, drying time was lower than blanched and sulphited samples but higher than blanched plus sulphited samples. Pretreatment was also found effective on the color changes (preservation or degradation). Blanching gave a bright color compared to fresh sample but less bright compared to sulphited samples. In case of SO2 retention, blanched plus sulphited sample showed higher retention than sulphited sample. Sulphited sample retains 44.8 ppm SO2/100g of sulphited sample, while the blanched plus sulphited sample retains 280 ppm SO2/100 g of blanched plus sulphited sample. J. Bangladesh Agril. Univ. 17(1): 105–109, March 2019